A irrepetibilidade dos valores pagos por erro da administração pública como um dos efeitos da extinção dos atos administrativos de concessão de benefícios previdenciários: uma abordagem de acordo com os ditames do neoconstitucionalismo - Levin, Eduardo (2021)
This paper aims to investigate one of the possible effects of administrative acts of invalidation of the acts of granting social security benefits: the possibility of collecting, with the beneficiaries, the amounts paid for error of the Administration. The consecration of the Social State of Law, a frequent concession of the most diverse advantages to those administered, gives birth, at least to those who have acted in good faith, the right to irrepeatability of the advantages they have enjoyed, in view of the fundamental right to the legal stability of relations between the Administration and those administered. In fact, the thesis that, once the act of granting a social security benefit, its invalidation is fully defensible, and that its invalidation will only have effects only for the future, so as to prevent the Administration from charging the insured, who has received the benefit of the legislation without having disputed the practice of illegality committed, the largest amounts received. If the acts in question were the work of the Public Power itself, which is why they were endorsed with the presumption of veracity and legitimacy that accompanies the administrative acts, it is natural that the administerer in good faith acted in their conformity, enjoying what resulted from such acts. In the end, it was concluded that, as a rule, it is the responsibility of the Administration to only fulminate the illegal act in order to prevent it from continuing to produce effects, she cannot impose on the beneficiary to return what it received